Critical Care in Human Immunodeficiency Virus–Infected Patients - Akgün, Kathleen M.; Miller, Robert F. (Seminars in Respiratory and Critical Care Medicine, 2016)
Intensive care unit (ICU) survival has been improved significantly for HIV-infected patients since the advent of antiretroviral therapy (ART). Non-AIDS conditions account for the majority of ICU admission diagnoses in areas with access to ART. However, opportunistic infections such as Pneumocystis jirovecii pneumonia still account for a significant proportion of ICU admissions, particularly in newly diagnosed HIV-infected patients, and are associated with increased ICU mortality. We discuss risk factors and outcomes for HIV-infected admitted to the ICU in the current ART era. We review the changing patterns in ICU admission diagnoses over time and how common ICU conditions are managed in HIV-infected compared with uninfected patients. We next address issues specific to the care for HIV-infected patients in the ICU, focusing on immune reconstitution inflammatory syndrome, ART continuation or initiation, and some common and potentially life-threatening ART-associated toxicities.
Keywords: HIV; antiretroviral therapy; outcomes; opportunistic infections